Serum metabolomics reveals the intervention mechanism and compatible regularity of Chaihu Shu Gan San on chronic unpredictable mild stress-induced depression rat model. (17th May 2020) - Zhang, Hongye; Huang, Huimin; Song, Hui; Chin, Bonnie; Zheng, Hua; Ruan, Junxiang; Wu, Fang; Cheng, Bang; Wu, Jinxia; Liu, Xuwen; Liang, Yonghong; Song, Fangming; et al.
Abstract: Objectives: To provide a comprehensive study of the intervention mechanism and compatible regularity of Chaihu Shu Gan San (CSGS) in a chronic unpredictable mild stress (CUMS)-induced depression model. Methods: Ethological study and ELISA assay were applied to measure the phenotypes of depression after CUMS stimulate and assess the antidepressant activity of fluoxetine, CSGS and its compatibilities. The serum metabolic profile changes were revealed by untargeted Q/TOF MS-based metabolomics followed by multivariate statistical analysis. Key findings: CSGS exhibits an significant intervention effect on CUMS-induced depression. After the multivariate statistical analysis, 17 potential serum biomarkers were identified and 16 of them could be regulated by CSGS. The intervention of CSGS on CUMS-induced depression involved five key pathways. Moreover, each functional unit (monarch, minister, assistant and guide medicine) in CSGS regulates different metabolites and metabolic pathways to achieve different effects on antidepressant; however, their intervention efficacies are inferior to the holistic formula, which may be due to the synergism of bioactive ingredients in the seven herbs of CSGS. Conclusions: CSGS produced an obvious antidepressant activity. The comprehensive and holistic metabolomics approach could be a powerful tool to study the intervention mechanism and the compatibility rule of traditional Chinese medicine.